2018
DOI: 10.3389/fbioe.2018.00156
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Networks From Endothelial Cells and Mesenchymal Stromal Cells From Adipose Tissue and Bone Marrow: A Comparison

Abstract: A promising approach to overcome hypoxic conditions in tissue engineered constructs is to use the potential of endothelial cells (EC) to form networks in vitro when co-cultured with a supporting cell type in a 3D environment. Adipose tissue-derived stromal cells (ASC) as well as bone marrow-derived stromal cells (BMSC) have been shown to support vessel formation of EC in vitro, but only very few studies compared the angiogenic potential of both cell types using the same model. Here, we aimed at investigating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 50 publications
2
49
1
Order By: Relevance
“…This model mimics vascularization strategies often deployed for tissue engineering applications that involve injection of populations of cells or pre‐patterned cell aggregates that organize into microvasculature. The phenotype and angiogenic potential of microvascular ECs and stromal cells vary widely according to their origin. We chose umbilical vein‐derived ECs and supporting cells derived from bone marrow, lung, and dermis to explore in our model because our prior work has suggested differential utilization of MMP‐ and plasmin‐mediated proteolysis with these combinations .…”
Section: Discussionmentioning
confidence: 99%
“…This model mimics vascularization strategies often deployed for tissue engineering applications that involve injection of populations of cells or pre‐patterned cell aggregates that organize into microvasculature. The phenotype and angiogenic potential of microvascular ECs and stromal cells vary widely according to their origin. We chose umbilical vein‐derived ECs and supporting cells derived from bone marrow, lung, and dermis to explore in our model because our prior work has suggested differential utilization of MMP‐ and plasmin‐mediated proteolysis with these combinations .…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of miR-188-5p might hence contribute to the endothelial barrier dysfunction and lymphangiopathy, which has been described in lipedema 44 . This suggests also a potential involvement of the mesenchymal stem cell populations of the SVF in the progression of lipedema, which are participating in the formation and stabilization of vessels 45 . It has been demonstrated that the total number of circulating particles (incl.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, this difficulty can be mastered by binding of cell recognition motifs in form of small immobilized peptides such as the RGD sequence, which stimulates cell adhesion via integrins (11). The most employed natural scaffolds for engineering vascular networks are collagens (12,13) or fibrin matrices (14,15,16). These types of scaffolds have a high degree of biocompatibility and provide superior adhesion sites leading to improved growth and differentiation capability of the cells (17).…”
Section: Scaffolds For 3d Engineeringmentioning
confidence: 99%
“…Initially, fibroblasts were utilized as supporting cell types for capillary formation in co-culture with ECs (16,25). Later, also mesenchymal stromal/stem cells (MSCs) mainly from bone marrow (14,26) and adipose tissue Overview of different vascularization strategies. Functional blood and lymphatic microvasculature can be achieved by co-culturing of endothelial and supporting cells from different origins.…”
Section: Different Sources Of Supporting Cell Typesmentioning
confidence: 99%